Instability of MX and M23C6 type precipitates in F82H steels under 2.8 MeV Fe2+ irradiation at 673 K. (December 2018) - Kano, Sho; Yang, Huilong; Shen, Jingjie; Zhao, Zishou; McGrady, John; Hamaguchi, Dai; Ando, Mamami; Tanigawa, Hiroyasu; Abe, Hiroaki
Highlights: The average size and number density of radiation defectsof 20 dpa irradiated specimen were respectively 5.8 nm and 6.9 × 10 21 m −3 . The shrinkage rate of MX-and M23 C6 -type precipitates under current irradiation condition was estimated as less than 0.1 nm/dpa. The Ostwald ripening was occurred in M23 C6 precipitates under the ion irradiation. The behaviors observed in electron irradiation such as amorphization and formation of low-contrast region on M23 C6 precipitates were undetected in the present study. Abstract: The purpose of this study is to investigate the response of the precipitates against irradiation in F82H steels which are considered as main candidate structure material for the fusion DEMO reactor blanket. M23 C6 -type precipitates contained F82H-IEA steel, and MX- and M23 C6 -type precipitates contained F82H-BA12 steel were selected as experimental specimens. Iron irradiation at 673 K using ion accelerator was performed on both steels up to 50 dpa. After irradiation, the instability behavior of precipitates was characterized using transmission electron microscopy. It is found that in F82H-IEA specimens, the number density of radiation defects at 20 dpa was 3.26 × 10 21 m −3, and the amorphization of M23 C6 was undetected up to 50 dpa. Although Ostwald ripening occurred in M23 C6 precipitates, the average size of M23 C6 mildly decreased with irradiation dose within this study. For F82H-BA12 specimens, the shrinkage rate of MX- and M23 C6 -type precipitates was estimated respectively as 0.06 and 0.03 nm/dpa. Hence, the MX and M23 C6 -type precipitates in F82H steel exhibit an excellent irradiation resistance under the present irradiation condition. Moreover, the behaviors like amorphization and weakening in contrast were not observed in M23 C6 precipitates in both specimens, which is different from electron irradiation, presumably due to the factors such as different damage rate.